Analisis Model CIPP dalam Evaluasi Pelaksanaan Aplikasi SiPita Tahun 2024 pada Kantor Perwakilan BKKBN Provinsi Kalimantan Selatan - Fitria Ramadhani; Taufik Arbain (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The implementation of effective, transparent, and digital-based public information services is one of the efforts to support the Electronic-Based Government System (SPBE). One of the innovations implemented by the South Kalimantan Provincial Representative Office of the National Population and Family Planning Board (BKKBN) is the SiPita application, which still faces several challenges in its implementation. This study aims to analyze the implementation of the SiPita application in 2024 using the CIPP (Context, Input, Process, Product) evaluation model. This study employed a qualitative approach with data collected through interviews, observations, and documentation. Data were analyzed using the CIPP evaluation model, which encompasses the aspects of context, input, process, and product. The findings indicate that the implementation of the SiPita application has generally supported the digitalization of public information services and enhanced information transparency within the South Kalimantan Provincial Representative Office of BKKBN. The implementation is supported by adequate human resources, infrastructure, standard operating procedures, and organizational policies. Service delivery processes have been carried out systematically through verification and validation mechanisms, the use of e-tickets, and regular monitoring and evaluation. However, several challenges remain, including limited server development, delays in data updates, suboptimal utilization of the application across all districts and municipalities, and the need to strengthen service resources. The implementation of SiPita has positively contributed to improving the quality of public information services, efficiency, transparency, data validity, and service accountability. Therefore, strengthening infrastructure, optimizing the system, and enhancing human resource capacity are necessary to ensure the sustainability of its implementation.